2019
DOI: 10.7567/1347-4065/ab163c
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of sidewall striation in high-aspect-ratio hole etching

Abstract: We investigated the formation mechanism of sidewall striations in etched holes with high aspect ratios, with focus on the roles of energetic ions and fluorocarbon radicals. Striations were observed on the sidewalls of holes with high aspect ratios in stacked dielectric films, despite the smooth sidewall of the mask. Argon plasma treatment increased the degree of striation on the carbon mask, while striation was prevented with a cyclic process consisting of a fluorocarbon deposition step and an argon plasma tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 34 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…The technique for creating HAR structures is the reactive ion etching (RIE) process. However, various issues such as insufficient mask selectivity, 2) shape bowing, 3) bending, 4) striation, 5) and aspect ratio-dependent etching rate reduction by RIE-lag 6) frequently occur in this process. Some of these phenomena are caused by charging-up on the sidewall of the hole 7,8) due to the angular broadening of incident-positive ions on the wafer.…”
Section: Introductionmentioning
confidence: 99%
“…The technique for creating HAR structures is the reactive ion etching (RIE) process. However, various issues such as insufficient mask selectivity, 2) shape bowing, 3) bending, 4) striation, 5) and aspect ratio-dependent etching rate reduction by RIE-lag 6) frequently occur in this process. Some of these phenomena are caused by charging-up on the sidewall of the hole 7,8) due to the angular broadening of incident-positive ions on the wafer.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results confirmed that mask morphology plays a role in hole shape, but a literature survey suggests that stochastic ion scattering can also affect the hole shape. [12][13][14][15]24) Figure 10 shows a simplified HAR etch simulation where the hard mask shape stays constant. That is, the hard mask is perfectly circular, and hard mask shadowing species should not contribute to any hole distortions.…”
Section: Feature-scale Modelmentioning
confidence: 99%
“…16) Silicon dioxide (SiO 2 ) is a key material for gate oxides, interlayer dielectrics, and spacer applications. 6,17) Considering its use in next-generation devices and the increasing complexity of design structures, plasma-assisted ALE processes for SiO 2 are continuously investigated for various targets. Among them, the periodic exposure of SiO 2 to C 4 F 8 /Ar plasma followed by low energy argon (Ar) ion bombardment that leads to a few nanometer etching of SiO 2 per cycle is popularly demonstrated by the group of Oehrlein.…”
Section: Introductionmentioning
confidence: 99%